A Comparative Study of Operational Efficiency of Pakistani and Malaysian Islamic Banks: Data Envelopment Analysis Approach - Haider, Muhammad Afaq; Raza, Qasim; Jameel, Soniya; Pervaiz, Khansa (Asian Economic and Financial Review, 2019)
This study compares the execution and potency of the Islamic banking operations currently practiced by Pakistan and Malaysia Islamic banks. In the 1980s both countries embarked their work on the Islamic banking system by using different entirely approaches. Malaysia adopted moderate solicitations towards the implementation of the Islamic financial system according to the shariah and law, which allows Islamic and the conventional banking system to operate on a parallel basis. On the other side, Pakistan engaged in converting the financial system in accordance with the Islamic shariah and law all at once. This study assays the approaches pursued by both countries towards the adoption of the Islamic banking system. For this meticulous prospect DEA (Data envelopment analysis), Malmquist total factor productivity index is used. To inspect the competency of the banks and further performance of these banks in comparison, eleven financial ratios are used in this study. We find that the productivity level of the Islamic banking system of Pakistan has increased as compared to the Malaysian Islamic banks by using data envelopment analysis.